THE METHOD OF ARABIC PEGON APPLICATION IN THE STUDY IN KRAPYAK ALI MAKSUM BOARDING SCHOOL, YOGYAKARTA - Ahmad Nurozi; Nurhasanah Walijah; Bella Munita Sary; Qurrotul ayuni (Fakultas Syariah Institut Agama Islam Darussalam Martapura, 2020)
Abstrak This research discusses the method of Arabic Pegon application for the learning process in Krapyak Ali Maksum Boarding School, Yogyakarta. This research focuses on the application of Arabic Pegon in understanding holy turats for the students outside Java who are not good at the Javanese language. This research aims to investigate the method of Arabic Pegon application which has been learned in the Krapyak Ali Maksum Boarding School in the learning and teaching processes, so it makes students able to understand the kinds of holy turats. This research used the qualitative approach with study case. The technical data accumulation used observation method and interview in which the subject of research is Kyai, the leader of boarding school. This research shows the result that the method of Arabic Pegon application learned in Krapyak Ali Maksum Boarding School has been effective because it is known that every student is able to follow this learning method. Key word : the method, Arabic Pegon, application, holy turats.